STAFF’S UNDERSTANDING OF ENGLISH LOAN WORD IN FINANCIAL TERMS (A STUDY AT PT. SARANA SULTENG VENTURA) - Nahdawati Nahdawati (Scolae: Journal of Pedagogy, 2019)
This research is descriptive qualitative research. It aims at finding out level of staff’s understanding of English loanword in financial terms incorporated borrowing. The objectives of this research are: to enlist the English financial loanterms commonly used by the staff of PT. Sarana Sulteng Ventura, to find out staff’s understanding on English loanfinancial terms by the staff of PT. Sarana Sulteng Ventura, and to find out the causes of difficulties encountered by thestaff of PT. Sarana Sulteng Ventura to comprehend English loan financial terms. In-depth interview, questionnaire, anddocument analysis data were collected and analyzed descriptively. There were 10 staffs that researcher took asrespondents at PT. Sarana Sulteng Ventura. Based on the result of data analysis, it was found that the staff’sunderstanding about English loan word in financial terms at PT. Sarana Sulteng Ventura was 80% categorized highlevel and 20% staffs categorized medium level.